Student Free Sex in the Perspective of Criminology and Law - Setyawan, Sendy Agus; Gustaf, Muhammad Akbar Maulana; Pambudi, Enggar Dias; Anwar, Syaiful; Fatkhurrozi, Mu’amar (Law Research Review Quarterly, 2019)
One of the negative things is free association where teenagers are free to do anything without taking into account the consequences of what they do. Free promiscuity that occurs a lot among adolescents is drinking liquor, free sex, even to a higher level, namely consuming Narcotics and Forbidden Drugs. Understanding association means the life of friends or community. And while free is loose and unobstructed, so it can speak, move, and do things freely, without being bound by rules. So it can be concluded that the meaning of free association is a friendship behavior that is not bound by the rules and social norms that apply in society, in this case it is the custom of east that upholds the norm of decency. The definition of free sex according to Kartono (1977) is a behavior that is driven by sexual desire, where these needs become more free when compared to traditional regulatory systems and are contrary to the norm system that applies in society. Whereas according to Desmita (2005) the notion of free sex is all ways of expressing and releasing sexual urges that originate from sexual maturity, such as intimate dating, making out, to having sexual contact, but these behaviors are considered inappropriate with the norm because adolescents do not have sexual experience.